DEMOKRASI EKONOMI ANTARA KEBERANIAN DAN BAYANGAN KEGAGALAN - Damianus J. Hali (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
Economic democracy concept is really special for Indonesia. It is not too many States to apply that terminology in their economic activities. Of course, that Moh. Hatta's opinion has a reason: Nevertheless in fact today, economic democracy ( Demokrasi Pancasila ) has to fight in powerful of current in Middle globalization and pressure international economic regim. If we have seen Basic of economic democracy concept which is